The effect of xenon‐augmented sevoflurane anesthesia on intraoperative hemodynamics and early postoperative neurocognitive function in children undergoing cardiac catheterization: A randomized controlled pilot trial. Issue 8 (13th July 2018) - Devroe, Sarah; Lemiere, Jurgen; Van Hese, Laura; Gewillig, Marc; Boshoff, Derize; Poesen, Koen; Van de Velde, Marc; Rex, Steffen
Summary: Background: In adults, xenon has only minimal hemodynamic side effects when compared with other anesthetics. Moreover, in preclinical experiments, xenon has been demonstrated to possess cardio‐ and neuroprotective properties. Altogether, the favorable hemodynamic profile combined with its potential for organ‐protection could render xenon an attractive option for anesthesia in children with cardiovascular compromise. Aims: The aim of this study was to explore safety and feasibility of sevoflurane‐augmented xenon anesthesia in school‐aged children and to assess early postoperative neurocognitive effects of xenon‐sevoflurane and sevoflurane anesthesia when compared to a control group that did not have anesthesia. Methods: Forty children aged 4‐12 years, suffering from congenital heart disease, undergoing diagnostic or interventional cardiac catheterization were randomized to either xenon‐augmented sevoflurane anesthesia or sevoflurane alone. Safety was assessed by the incidence of intraprocedural hemodynamic instability and feasibility by anesthetic depth and respiratory profile. In addition, neurocognitive performance was assessed preoperatively, 2 hours after discharge from PACU and at 24 hours after anesthesia using the Amsterdam Neuropsychological Tasks system. A healthy control group of 22 age‐ and gender‐matched children not exposed to anesthesia underwent an identical neurocognitive test battery, at comparable time intervals. Results: Overall hemodynamics did not differ between groups. Xenon‐sevoflurane anesthesia resulted in decreased intraoperative ephedrine requirements (median [IQR]) (0.00 mg/kg [0.00‐0.00] vs 0.00 mg/kg [0.00‐0.01], P = 0.047). Only neurocognitive tests in the domain of alertness were significantly impaired 2 hours postoperatively in both anesthesia groups in comparison with the control group (alertness variability: P = 0.02, odds ratio 5.8), but recovered at 24 hours. For working memory, inhibition, cognitive flexibility, and motor coordination tasks, no significant interaction effects of anesthesia were found in the early postoperative period. Conclusion: In this pilot trial, xenon‐augmented sevoflurane anesthesia in school‐aged children was feasible, and associated with decreased ephedrine requirements. All children exposed to anesthesia showed impaired neurocognitive performance in the immediate postoperative period when compared to control children; however, without significant differences between both treatment groups.